Modelo de estrategias de servicio de atención al usuario para las secretarias del Gobierno Autónomo Descentralizado Municipal del cantón El Empalme provincia del Guayas, año 2015 - Basurto Zambrano, Ana Elizabeth (2015)
The quality customer service is one of the key points that must be met in enterprises; regardless of the size, structure and nature of their operations, must demonstrate the ability to perform in this area as being the first image that gives customers helps keep the same preference, and if you get to change can become a threat. In this sense, this research was proposed as Objective: To establish guidelines for a model of customer service strategies for administrative staff Decentralized Autonomous Government of El Empalme Canton, Guayas Province, 2015. The results reported that secretaries Decentralized Autonomous Municipal Government of El Empalme Canton, do not provide quality service as needed to apply the manual established by the institution, also the lack of a guide with strategies for customer service, creating some level of discomfort on users. It has established four basic and fundamental strategies applicable in the municipal GAD to promote quality service to users and enhance the corporate image, which appear in the Plan of strategies aimed at secretaries and human resource council to improve service users to Decentralized Autonomous Municipal Government of Guangzhou Empalme, so it is suggested to accept the accompanying strategies. Keywords: Customer Service, Technical Customer Service, Service Strategy